Towards a Discovery of a Zinc-Dependent Phosphate Transport Road in Plants - Hui-Kyong Cho; Jaspreet Sandhu; Nadia Bouain; Chanakan Prom-u-thai; Hatem Rouached (Plants, 2022)
Owing to the impending global scarcity of high-quality sources of phosphate (Pi) fertilizers, lowering its use in crop production requires improved insights into factors stimulating Pi uptake from the soil as well as the efficacious use by plants. Following decades of extensive research on plants’ adaptation to Pi deficiency with mitigated success in the field, a better understanding of how plants exposed to zinc (Zn) deficiency accumulate much more Pi provides a novel strategy in comparison to when plants are grown in Zn-rich soils. In this context, we review current knowledge and molecular events involved in the Pi and Zn signaling crosstalk in plants that will bear great significance for agronomical and rudimentary research applications.